2016
DOI: 10.5653/cerm.2016.43.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone as a predictor of polycystic ovary syndrome treated with clomiphene citrate

Abstract: ObjectiveThis study aimed to determine the threshold of anti-Müllerian hormone (AMH) as predictor of follicular growth failure in polycystic ovary syndrome (PCOS) patients treated with clomiphene citrate (CC).MethodsFifty female subjects with PCOS were recruited and divided into two groups based on successful and unsuccessful follicular growth. Related variables such as age, infertility duration, cigarette smoking, use of Moslem hijab, sunlight exposure, fiber intake, body mass index, waist circumference, AMH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…A high pre-treatment AMH merits initiating OI with higher doses of CC or LET than used in ovulatory women. [ 50 51 52 53 54 ] Alternatively, gonadotropins may be more effective in inducing ovulation in such women. In the context of IUI, very high levels of AMH >10 ng/ml may predict a poor response even with gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high pre-treatment AMH merits initiating OI with higher doses of CC or LET than used in ovulatory women. [ 50 51 52 53 54 ] Alternatively, gonadotropins may be more effective in inducing ovulation in such women. In the context of IUI, very high levels of AMH >10 ng/ml may predict a poor response even with gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using AMH Gen II assay found a level of 8.58 ng/ml to have 78% sensitivity and 67% specificity for the prediction of non-response to CC. [ 52 ] A small retrospective study further reported an AMH level of 9.78 as the discriminatory level beyond which cumulative ovulation rates were significantly lower. [ 53 ] Finally, in a large cohort study of women with PCOS using Gen II AMH assay, it was noted that women with higher AMH levels needed higher doses of CC or LET to achieve ovulation and the chances of ovulation reduced with increasing levels of AMH.…”
Section: A Nti -M Ullerian H ...mentioning
confidence: 99%
“…The selected AMH cut-off was 86.7 pmol/L, but sensitivity and specificity were not satisfactory for clinical application (65.5% and 52%, respectively). The AMH thresholds proposed in the literature to predict total resistance to CC (150 mg/day dose) are highly variable (from 24.3 pmol/L to 88.4 pmol/L) with no satisfactory relative sensitivities and specificities [21,41,[46][47][48]. In addition, some authors found no significant difference in serum AMH levels between women ovulating on CC versus those resistant to treatment [49].…”
Section: Discussionmentioning
confidence: 99%
“…The AMH thresholds proposed in the literature to predict complete resistance to CC (150 mg/day dose) are highly variable (from 24.3 to 88.4 pmol/L or 3.4 to 12.4 ng/mL) with unsatisfactory sensitivities and specificities. [21][22][23][24][25][26] In addition, some authors found no significant difference in serum AMH levels between women ovulating on CC and those who were resistant to treatment. 27 The difference in the AMH test kits used in the different studies (which have different sensitivities) may explain these results.…”
Section: Is Amh Testing Useful For Predicting Response To Oral Ovulat...mentioning
confidence: 99%